2016
DOI: 10.12693/aphyspola.130.1110
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Electron Microscopy Investigation of Topologically Close-Packed Phases in CMSX-4 Single Crystal Superalloy

Abstract: In this work the topologically close-packed phases precipitated during annealing of CMSX-4 single-crystal superalloy at temperature 1100• C were investigated. Microstructural analyses were carried out by means of scanningand transmission electron microscopy as well as scanning-transmission electron microscopy in high angle annular dark field mode. Chemical composition in nanoareas was determined using energy dispersive X-ray spectroscopy. Scanning electron microscopy investigation has shown that the topologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…1B,C. The microstructure and chemical composition of TCP phases was the subject of our previous work [12]. We have demonstrated the compositional variations of γ, γ and TCP phases for the as-received condition and annealed at 1100…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…1B,C. The microstructure and chemical composition of TCP phases was the subject of our previous work [12]. We have demonstrated the compositional variations of γ, γ and TCP phases for the as-received condition and annealed at 1100…”
Section: Resultsmentioning
confidence: 75%
“…Although Ta is γ -forming element, in the present study the increase of its concentration in γ phase was observed with prolongation of the annealing time. Additionally, in our previous work the contribution of Ta to the formation of TCP phases in CMSX-4 was revealed [12]. Therefore it may be suspected that the diffusion of Ta also plays an important role in the microstructural instability of CMSX-4 superalloy at high temperature.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In our previous works on the chemical composition of the TCP phases in CMSX‐4 subjected to high temperature annealing (Dubiel et al ., ), as well as annealing followed by creep deformation (Dubiel et al ., ), based on STEM‐EDS microanalysis results, it was confirmed that the P and μ phases are rich in W and Re. The differences in the W and Re concentrations in both phases were less than 5 at.…”
Section: Resultsmentioning
confidence: 99%